Effect of heat treatment on repetitively scanned SLM NiTi shape memory alloy - An, Jia (2019)
Selective Laser Melting (SLM) has been implemented to address the difficulties in manufacturing complex nickel titanium (NiTi) structures. However, the SLM production of NiTi is much more challenging than the fabrication of conventional metals. Other than the need to have a high density that leads to excellent mechanical properties, strict chemical compositional control is required as well for the SLM NiTi parts to exhibit desirable phase transformation characteristics. In addition, acquiring a high transformation strain from the produced specimens is another challenging task. In the prior research, a new approach—repetitive scanning—was implemented to achieve these objectives. The repetitively scanned samples demonstrated an average of 4.61% transformation strain when subjected to the tensile test. Nevertheless, there is still room for improvement as the conventionally-produced NiTi can exhibit a transformation strain of about 6%. Hence, post-process heat treatment was introduced to improve the shape memory properties of the samples. The results showed an improvement when the samples were heat treated at a temperature of 400 °C for a period of 5 min. The enhancement in the shape memory behavior of the repetitively scanned samples was mainly attributed to the formation of fine Ni4Ti3 metastable precipitates.